ANALYSIS OF BUSINESS INCOME FROM STRONGWINE, CASCARA AND GREEN COFFE PROCESSING BUSINESSSES IN CENTRAL ACEH (CASE STUDY OF UMKM ASSISTED BY KBQ BABURRAYYAN) - Dedy Darmansyah; Yoga Nugroho; Rusdi Faizin; Cut Ana Fitria (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The purpose of this study was conducted to analyze the level of profit in the business of processing Arabica coffee derivative products at the KBQ Baburrayyan UMKM in Berawang Dewal Village, Central Aceh, where this analysis can find out in detail the costs of production, income, business income. This research was conducted for about 4 months from August to November located in Central Aceh. Data sources in this study used primary data obtained by conducting direct interviews with business owners using a list of questions that had been prepared, and secondary data obtained from literary studies, written sources and agencies at the research location. The method used in this research is a case study method with quantitative descriptive analysis, using an analysis of the calculation of total costs, total income, revenue, R/C ratio. The results showed that the total production cost for strong wine was Rp. 4,044,453, -/month, total income of Rp. 13,000,000, -/month, and income Rp. 8,955,547,-/month. Cost calculation for cascara products, the total production cost is Rp. 4,450,734, -/month, total income Rp. 33,000,000, -/month, and income Rp. 28,549,266,-/month. The results of calculations on green coffee products total production costs of Rp. Rp. 2,475,773,-/month, total income of Rp. 5,250,000.-/month, and income of Rp. 2,774,227,-/month. From the results of the R/C Ratio analysis of the three arabica coffee derivative products, the average R/C Ratio gets a value of more than 1 (R/C>1), namely the strong wine product gets a value of 3.21 which means the business is profitable, for cascara products it gets the R/C Ratio value is 7.